A REPRESENTATIVIDADE DOS POVOS INDÍGENAS NO DOCUMENTO CURRICULAR DO TERRITÓRIO MARANHENSE (DCTMA): Implicações na prática docente de uma escola da rede municipal de Imperatriz - COSTA, Thalia Braga (2025)
The Maranhão Territory Curricular Document (DCTMA), the object of this research, guides the school curriculum from Early Childhood Education to Elementary Education in Maranhão. This document should be used as a basis by public and private schools in the (re)organization of their Political Pedagogical Projects (PPP) and in the preparation of teachers' lesson plans. Maranhão has more than 57 thousand self-declared indigenous people and eleven culturally distinct indigenous peoples, which is why the work raises the following problem: What is the representation of indigenous peoples in the DCTMA and in teaching practice in a school in the municipal network of Imperatriz - MA? Based on the problem, we seek to analyze the representation of indigenous peoples in the DCTMA and in teaching practice in a school in the municipal network of Imperatriz - MA. Specifically, the research seeks to analyze how the process of preparation and implementation of the DCTMA occurred; to verify the representation of indigenous peoples in this document, examine how the document relates to teaching practice and prepare a book entitled: “Guiding documents: between discourse and reality in the voices of teachers”. We adopted documentary research, using the document as the main source of analysis, with the following categories of analysis: cultural diversity of indigenous peoples; indigenous peoples of Maranhão; indigenous people and Indian. Field research was also carried out in a municipal school in Imperatriz. We used unstructured interviews as a data collection technique, with four teachers from the aforementioned school, a coordinator of the Imperatriz Regional Unit (UREI) and the organizer of the Working Groups in Imperatriz, during the period when the DCTMA was being prepared. We concluded that in the preparation and implementation of the DCTMA, teachers were not considered in the process of writing the document. There were moments of listening, but their contributions were not included in the text of the document. When we examined the document regarding the representation of indigenous peoples in the DCTMA, we found that some social stereotypes were reinforced and that the cultural diversity of the indigenous peoples of Maranhão was not discussed as much. The teachers consider the document analyzed as just another bureaucratic instrument in their daily professional lives and that there is no ongoing training that addresses the state's diversity, in addition to not providing teaching resources to address the indigenous histories and cultures of the peoples of Maranhão. The product found that teachers are not invited to think about and discuss the preparation of documents that guide their practice and that initial and ongoing training does not consider cultural diversity and the ways in which it should be present in schools.